2017
DOI: 10.1155/2017/7826840
|View full text |Cite
|
Sign up to set email alerts
|

Partner Selection in Supply Chain of Vietnam’s Textile and Apparel Industry: The Application of a Hybrid DEA and GM (1,1) Approach

Abstract: Vietnam is currently among the top-five textile and apparel exporters, and the industry is considered quite attractive to foreign investors. Nevertheless, the global textile and garment industry is experiencing important changes. The three main producing regions in the world are China, Southwest Asia (India, Pakistan, Bangladesh, and Turkey), and ASEAN. In order to maintain its positioning and to establish stable and sustainable Vietnam textile and apparel development, there must be radical changes. Due to thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 15 publications
0
13
0
Order By: Relevance
“…The best productivity is shown by Libya, however this DEA does not show benchmarking values and it is suggested that, to benchmark the countries for the same time period, multistage DEA can be performed. The forecast is calculated by the actual data, and if the errors are in the allowable range, then it will be a reliable and usable model for the study [43]. The forecasted results of this study have a high level of accuracy, as average MAPE of 20 DMUs is 8.21% as in Table 5.…”
Section: Pearson Correlationmentioning
confidence: 79%
“…The best productivity is shown by Libya, however this DEA does not show benchmarking values and it is suggested that, to benchmark the countries for the same time period, multistage DEA can be performed. The forecast is calculated by the actual data, and if the errors are in the allowable range, then it will be a reliable and usable model for the study [43]. The forecasted results of this study have a high level of accuracy, as average MAPE of 20 DMUs is 8.21% as in Table 5.…”
Section: Pearson Correlationmentioning
confidence: 79%
“…These studies have yielded good results and high applicability. Among them, Chia-Nan Wang, Han-Khanh Nguyen, and Ruei-Yuan Liao [7] combined the Grey model and DEA model to find a strategic partner in the supply chain of the textile and garment industry in Vietnam. In 2011, Jia-Jane Shuai and Wei-Wen Wu [8] used the DEA model and Grey model to evaluate marketing effectiveness through the website of hotels in Taiwan.…”
Section: Related Researchmentioning
confidence: 99%
“…Through the Website of the General Statistics Office, the authors compiled 17 contractors to satisfy the conditions of this study ( Table 2). Coteccons construction joint stock company I 5 Hoa Binh construction group joint stock company I 6 Binhduong trade and development joint stock company I 7 Development investment construction Hoi An joint stock company I 8 Licogi 14 joint stock company I 9 Tien Giang investment and construction joint stock company I 10…”
Section: Contractors Collectionmentioning
confidence: 99%
“…e T&C sector in Pakistan is one of the most prominent manufacturing industries that assume a central part in the country's economy as it offers employment to 30% of the country's total workforce, adds 8.5% to GDP, and continues to be the lifeblood for the country's exports at 52% of the total trade [6,7]. Pakistan is amongst the main textiles producing regions of the world, as quoted by Wang et al [8].…”
Section: Introductionmentioning
confidence: 99%